β2→1-Fructans Modulate the Immune System In Vivo in a Microbiota-Dependent and -Independent Fashion - Fransen, Floris; Sahasrabudhe, Neha M.; Elderman, Marlies; Bosveld, Margaret; El Aidy, Sahar; Hugenholtz, Floor; Borghuis, Theo; Kousemaker, Ben; Winkel, Simon; van der Gaast-de Jongh, Christa; de Jonge, Marien I.; Boekschoten, Mark V.; et al. (Frontiers in Immunology, 2017)
It has been shown in vitro that only specific dietary-fibers contribute to immunity but studies in vivo are not conclusive. Here we investigated degree of polymerization (DP) dependent effects of β2→1-fructans on immunity via microbiota dependent and independent effects. To this end, conventional or germ-free mice received short or long-chain β2→1-fructan for 5 days. Immune cell populations in the spleen, mesenteric lymph nodes (MLN), and Peyer’s patches (PPs) were analyzed with flow cytometry, genome-wide gene expression in the ileum was measured with microarray, and gut microbiota composition was analyzed with 16S rRNA sequencing of fecal samples. We found that β2→1-fructans modulated immunity by both microbiota and microbiota independent effects. Moreover, effects were dependent on the chain-length of the β2→1-fructans type polymer. Both short and long-chain β2→1-fructans enhanced T-helper 1 cells in Peyer’s patches, whereas only short-chain β2→1-fructans increased regulatory T cells and CD11b-CD103- DCs in the MLN. A common feature after short and long-chain β2→1-fructan treatment was enhanced Fut2 expression and other IL-22 dependent genes in the ileum of conventional mice. These effects were not associated with shifts in gut microbiota composition, or altered production of short-chain fatty acids. Both short and long-chain β2→1-fructans also induced immune effects in germ free animals, demonstrating direct effect independent from the gut microbiota. Also, these effects were dependent on the chain-length of the β2→1-fructans. Short-chain β2→1-fructan induced lower CD80 expression by CD11b-CD103- DCs in PPs, whereas long-chain β2→1-fructan specifically modulated antibody production by B cells in germ-free mice. In conclusion, support of immunity is determined by the chemical structure of β2→1-fructans and is partially microbiota-independent.